Life history traits and reproductive mode of the tardigrade Acutuncus antarcticus under laboratory conditions: strategies to colonize the Antarctic environment - ALTIERO, Tiziana; GIOVANNINI, ILARIA; GUIDETTI, Roberto; REBECCHI, Lorena (Hydrobiologia, 2015)
Global climate change has become an important issue, particularly for organisms living in the Antarctic region, as the predicted temperature increase can affect their life history traits. The reproductive mode and life history traits of one of the most widespread species of tardigrades in Antarctica were analyzed. Specimens of the eutardigrade Acutuncus antarcticus from a temporary freshwater pond at Victoria Land (Antarctica) were individually cultured. This species reproduced continuously by thelytokous meiotic parthenogenesis. Its life cycle was short (60–90 days) and the reproductive output was low, with a short generation time (25–26 days). The maternal effect can be responsible of the phenotypic plasticity observed in life history traits of the three analyzed generations that may be seen as a bethedging strategy, as also observed in other animals inhabiting stochastic environments. These traits, along with the cryptobiotic capability of A. antarcticus, are advantageous for exploiting the conditions suitable for growth and reproduction during the short Antarctic summer, and can explain its wide distribution on the Antarctic continent. These results open new avenues of research for determining the role of bet-hedging strategy in organisms living in unpredictable environments.